Brushite bone cement with energy metabolism regulation function and application of brushite bone cement

By adding specific ingredients and admixtures to the calcium permeable phosphite bone cement, the problems of poor injectability, low mechanical strength and insufficient osteogenic performance are solved, and the efficient bone repair and clinical application performance of bone cement are achieved.

CN119770721APending Publication Date: 2025-04-08SUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411823225.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Calcium permeable phosphite cement has problems such as poor injectability, low mechanical strength and insufficient osteogenic performance in clinical applications, which limits its application in minimally invasive orthopedic surgery.

Method used

By adding β-tricalcium phosphate, dihydrogen phosphate and citrate to calcium permeable phosphite bone cement, and using polyacrylic-acrylamide as an admixture, the curing time and mechanical properties of the bone cement are adjusted, while enhancing its energy metabolism regulation function.

Benefits of technology

It has achieved good injectability of calcium permeable phosphite bone cement, improved mechanical properties, and enhanced its osteogenic properties in bone repair, which can meet the needs of minimally invasive orthopedic treatments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770721A_ABST
    Figure CN119770721A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bone cement materials, and particularly relates to brushite bone cement with an energy metabolism regulation function and application of the brushite bone cement. The bone cement mainly comprises a solid phase and a liquid phase. The solid phase is mainly beta-tricalcium phosphate and monocalcium phosphate, and the liquid phase is mainly citrate. After solid and liquid are mixed, the solid phase is dissolved. Under the acidic condition, the brushite is calcium phosphate with the lowest solubility, so that the solution quickly reaches a saturated state and begins to form a brushite crystal nucleus. Along with the continuation of the dissolution and recrystallization process, the brushite crystal nucleuses gradually grow up and are mutually staggered, and finally the cured brushite cement is formed. According to the invention, polyacrylic acid-acrylamide is used as an additive. The additive is added as a liquid phase to bone cement. The brushite bone cement has good injectability, mechanical properties and an energy metabolism regulation function, a brand new way is provided for preparation of novel bone cement, and the brushite bone cement can meet the requirements of clinical orthopaedic minimally invasive treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone cement materials, and in particular relates to a brushite bone cement with energy metabolism regulating function and application thereof. Background Art

[0002] Brushite bone cement is a kind of calcium phosphate (CaHPO 4 ·2H 2 (0) is the calcium phosphate cement of the final product. It solidifies through the dissolution-recrystallization process, and the solidified product formed can not only simulate the composition of natural bones, but also form a good integration with the surrounding bone tissue, and promote the formation of new bones. Compared with traditional hydroxyapatite bone cement, it has better biodegradability and osteogenic properties, and has become one of the materials that have attracted much attention in the fields of orthopedics and dentistry. These characteristics of brushite bone cement make it particularly suitable for various types of bone defect repair in clinical practice, such as fracture repair, bone defect filling after bone tumor resection, dental implant repair, etc. However, although brushite cement performs well in biocompatibility and osteogenic properties, its relatively low mechanical strength and poor injectability limit its application in minimally invasive orthopedic surgery for vertebral body shaping. In operations such as percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP), the materials used must have a series of key properties. First, the material needs to have excellent injectability and fluidity, can be smoothly injected and filled in the defect area under a small incision, and have a suitable hardening time to ensure the operability of the operation. Secondly, the material must have sufficient mechanical strength to bear the weight of the spine and integrate well with the surrounding bone tissue. Biocompatibility is also an important factor. The material must avoid triggering immune responses or chronic inflammation and have appropriate degradability so that it can be gradually replaced by new bone during bone healing. In addition, the material should have good shaping ability, be able to adapt to the anatomical structure of the vertebral body, and ensure uniform distribution of bone cement. Radiopacity is also a requirement that cannot be ignored. The material should be clearly visible in X-rays or CT scans to facilitate precise operations by doctors. At present, polymethyl methacrylate (PMMA) is still regarded as the gold standard for surgeries such as PVP and PKP. The mechanical strength and injectability of brushite bone cement need to be further improved to meet clinical requirements.

[0003] Researchers have proposed a variety of improvement strategies to improve the mechanical properties and clinical operability of brushite bone cement. Current mechanical enhancement strategies mainly focus on reducing porosity or strengthening the inorganic network of cement. For example, researchers have found that the compressive strength of cement can be significantly improved by pre-stressing bone cement. However, in actual clinical operations, it is impossible to apply any pre-stress to the bone cement injected into the defect site, so this method is not suitable for the mechanical enhancement of injectable bone cement. Reducing the liquid-solid ratio can significantly improve the mechanical properties of bone cement, but too low a liquid-solid ratio will greatly affect the injectability and clinical operability of bone cement. In addition, ion doping and constructing an interpenetrating reinforcement network in cement can also improve the mechanical strength of bone cement to a certain extent, but the enhancement effect of these methods is limited, and some methods will have an adverse effect on the degradation performance and biocompatibility of cement. Therefore, it is urgent to explore new innovative strategies to further improve the mechanical properties and clinical operability of brushite bone cement.

[0004] In addition to mechanical strength and operability, osteogenic properties are also crucial for the clinical application of bone cement. After bone injury occurs, the bone microenvironment and blood vessels are damaged, leading to increased inflammation and local hypoxia. Bone marrow mesenchymal stem cells usually rely on anaerobic glycolysis. After bone injury occurs, the impaired tricarboxylic acid cycle and oxidative phosphorylation functions may lead to delayed healing or non-healing of fractures. The tricarboxylic acid cycle is crucial in energy metabolism and provides the required ATP for a variety of biological activities. The tricarboxylic acid cycle is the core of cell metabolism and supports the regeneration and repair of bone tissue by providing ATP to meet the energy needs of cell proliferation, differentiation and matrix synthesis. In the hypoxic environment of bone injury, cells often face the challenge of limited energy generation. By promoting the activity of the tricarboxylic acid cycle, energy supply can be improved and the normal metabolic function of bone marrow mesenchymal stem cells can be restored. In addition, enhancing the utilization of metabolites related to the tricarboxylic acid cycle not only helps to regulate the local metabolic environment of the bone injury site, but also accelerates the formation and mineralization of new bone by promoting osteogenesis-related signaling pathways and gene expression, thereby significantly improving the bone repair effect. However, current bone cements generally lack the ability to regulate energy metabolism. Therefore, it is of great significance to further develop bone repair cement with good injectability, high mechanical strength and energy metabolism regulation function.

[0005] Brushite bone cement is mainly formed by acid-base reaction in an acidic environment. 2 PO 4 ) 2 ·H 2 O, monocalciumphosphate monohydrate, MCPM] and β-tricalcium phosphate [β-Ca 3 (PO 4 ) 2, β-tricalciumphosphate, β-TCP] are commonly used acidic and alkaline calcium sources. Compared with hydroxyapatite cement, brushite bone cement has better degradation ability and can be degraded and form new bone within a few months. Its main disadvantage is that its short curing time leads to poor injectability, and similar to HA bone cement, its mechanical properties are relatively low. Therefore, current research is mainly to extend its curing time and improve its mechanical strength. Over the years, many scholars have enhanced brushite bone cement by reducing the particle size of the reactants [ActaBiomater 2009, 5 (1), 43-49], fiber reinforcement [Acta Biomater 2018, 79, 182-201], or using admixtures such as citric acid [Philos Trans AMath Phys Eng Sci 2010, 368, 1937-1961] and pyrophosphate [JAm Chem Soc 2005, 88 (11), 3096-3103], but its mechanical properties have not made a major breakthrough. A previous patent disclosed a new type of brushite bone cement, its preparation, and its application in the field of bone repair and bone regeneration (ZL 202110014054.3). The enhancement of this bone cement is mainly due to the addition of ammonium ferric citrate.

[0006] Strength and injectability cannot simultaneously meet the needs of clinical minimally invasive treatment. High-strength bone cements often have poor injectability, while bone cements with good injectability often have low strength. In addition, current bone cements lack the function of regulating energy metabolism and are still insufficient in terms of osteogenic and bone integration properties. Summary of the invention

[0007] In order to solve the above-mentioned problems of poor injectability, low mechanical strength and insufficient osteogenic performance of bone cement, the present application provides the following technical solutions:

[0008] The present invention provides a brushite bone cement with energy metabolism regulating function, wherein the brushite bone cement with energy metabolism regulating function is obtained by combining a solid phase and a liquid phase;

[0009] The solid phase includes β-tricalcium phosphate (β-TCP) and monocalcium phosphate, and the liquid phase includes citrate, polyacrylic acid-acrylamide (CAS No. 9003-06-9) and water.

[0010] Preferably, the monocalcium phosphate is selected from monocalcium phosphate monohydrate (MCPM).

[0011] The manufacturer of β-TCP is Suzhou Ding'an Technology Co., Ltd.; the manufacturer of MCPM is Scharlau in Spain; the sodium citrate brand is purchased from Sigma-Aldrich; and polyacrylic acid-acrylamide is purchased from Sigma-Aldrich.

[0012] Preferably, the mass ratio of the β-tricalcium phosphate to the calcium dihydrogen phosphate monohydrate is 3-7:3-7.

[0013] Furthermore, the mass ratio of the β-tricalcium phosphate to the calcium dihydrogen phosphate monohydrate is 6:4.

[0014] Preferably, in the liquid phase, the concentration of citrate is 0.3-1.0 mol / L.

[0015] Preferably, in the liquid phase, the concentration of polyacrylic acid-acrylamide is 1-15 wt %.

[0016] Furthermore, in the liquid phase, the concentration of polyacrylic acid-acrylamide is 2.5 wt %.

[0017] Preferably, the citrate is selected from sodium citrate.

[0018] Preferably, the solid phase also includes an X-ray blocking agent.

[0019] Furthermore, the X-ray blocking agent is selected from zinc oxide, strontium chloride, strontium bromide, strontium iodide or strontium phosphate.

[0020] The present invention also provides application of the above-mentioned brushite bone cement with energy metabolism regulating function in minimally invasive treatment of orthopedics.

[0021] The composition of traditional bone cement mainly includes solid phase and liquid phase. The solid phase is mainly β-tricalcium phosphate and monocalcium phosphate monohydrate. The liquid phase is mainly citrate. When the solid and liquid are mixed, β-TCP and MCPM dissolve. Under acidic conditions, brushite is the calcium phosphate with the lowest solubility, so the solution quickly reaches saturation and begins to form brushite nuclei. As the dissolution and recrystallization process continues, the brushite nuclei gradually grow and intertwine, eventually forming solidified brushite cement. The specific reaction is as follows:

[0022] β-Ca 3 (PO 4 ) 2 +Ca(H 2 PO 4 ) 2 ·H 2 O+7H 2 O→4CaHPO 4 ·2H 2 O

[0023] In the present invention, polyacrylic acid-acrylamide is mainly selected as an additive. The additive is added to the bone cement as a liquid phase.

[0024] The technical solution of the present invention has the following advantages over the prior art:

[0025] The present invention enables the brushite bone cement to have good injectability, mechanical properties and energy metabolism regulation function, and provides a new way for the preparation of new bone cement, so that it can meet the needs of clinical orthopedic minimally invasive treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a graph showing that the addition of 2.5% polyacrylic acid-acrylamide in Example 1 can significantly increase the content of ATP in cells.

[0027] Figure 2 This is a data graph showing that the addition of 2.5% polyacrylic acid-acrylamide in Example 1 can increase the surface adsorption amount of cement particles and the negative charge of cement particles.

[0028] Figure 3 The in vitro bone repair effects of brushite, hydroxyapatite and polymethylmethacrylate bone cement (alkaline phosphatase staining and alizarin red staining).

[0029] Figure 4 This is a graph showing the in vivo bone repair effects of brushite, hydroxyapatite and polymethylmethacrylate bone cement after 4 weeks. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0031] Example 1

[0032] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0033] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0034] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 2.5 wt %.

[0035] Example 2

[0036] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0037] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0038] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 1 wt %.

[0039] This embodiment is the same as embodiment 1, except that the addition amount of polyacrylic acid-acrylamide is 1 wt %.

[0040] Example 3

[0041] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0042] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0043] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 5 wt %.

[0044] This embodiment is the same as embodiment 1, except that the addition amount of polyacrylic acid-acrylamide is 5 wt %.

[0045] Example 4

[0046] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0047] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0048] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 10 wt %.

[0049] This embodiment is the same as embodiment 1, except that the addition amount of polyacrylic acid-acrylamide is 10 wt %.

[0050] Example 5

[0051] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0052] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0053] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 15 wt %.

[0054] This embodiment is the same as embodiment 1, except that the addition amount of polyacrylic acid-acrylamide is 15 wt %.

[0055] Example 6

[0056] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0057] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0058] In the liquid phase, the concentration of sodium citrate is 0.3 mol / L, and the amount of polyacrylic acid-acrylamide added is 1 wt %.

[0059] The solid phase also contains an X-ray blocking agent, which is zinc oxide.

[0060] Example 7

[0061] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0062] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0063] In the liquid phase, the concentration of sodium citrate is 1.0 mol / L, and the amount of polyacrylic acid-acrylamide added is 15 wt %.

[0064] The solid phase also contains an X-ray blocking agent, which is strontium chloride.

[0065] Example 8

[0066] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0067] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 1:1) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0068] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 2.5 wt %.

[0069] The solid phase also contains an X-ray blocking agent, which is strontium bromide.

[0070] Example 9

[0071] This embodiment is the preparation of a high-strength and highly injectable brushite bone cement using polyacrylic acid-acrylamide as an admixture.

[0072] In this embodiment, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 3:7) are used as the solid phase, and sodium citrate and polyacrylic acid-acrylamide are used as the liquid phase.

[0073] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 2.5 wt %.

[0074] The solid phase also contains an X-ray blocking agent, which is strontium phosphate.

[0075] Comparative Example 1

[0076] This comparative example is the preparation of brushite bone cement.

[0077] In this comparative example, β-tricalcium phosphate and calcium dihydrogen phosphate monohydrate (the mass ratio of the two phases is 6:4) are used as the solid phase, and sodium citrate is used as the liquid phase.

[0078] In the liquid phase, the concentration of sodium citrate is 0.5 mol / L, and the amount of polyacrylic acid-acrylamide added is 0.

[0079] This comparative example is substantially the same as Example 1, except that polyacrylic acid-acrylamide is not doped.

[0080] Application Example 1

[0081] The curing time, strength and injectability of bone cement as a function of polyacrylic acid-acrylamide concentration are shown in Table 1:

[0082] Table 1 Test data of curing time, strength and injectability of bone cement as a function of polyacrylic acid-acrylamide concentration

[0083] Components Curing time (min) Compressive strength(MPa) Injectability (%) Comparative Example 1 0% Polyacrylic acid-acrylamide 40 67 68 Example 2 1% Polyacrylic acid-acrylamide 36 73 76 Example 1 2.5% Polyacrylic acid-acrylamide 30 80 85 Example 3 5% Polyacrylic acid-acrylamide 25 76 85 Example 4 10% Polyacrylic acid-acrylamide 30 71 90 Example 5 15% Polyacrylic acid-acrylamide 42 66 88

[0084] Effect evaluation 1

[0085] In Example 1, polyacrylic acid-acrylamide is added as an admixture to brushite bone cement. Its addition can significantly regulate the release of citrate in bone cement, thereby enhancing its energy metabolism, wherein the mass concentration of polyacrylic acid-acrylamide is 2.5%. The preparation process of brushite bone cement is the same as that of Example 1. Figure 1 As shown, the addition of polyacrylic acid-acrylamide can significantly increase the intracellular ATP content.

[0086] Effect evaluation 2: Polyacrylic acid-acrylamide enhances mechanical strength and fluidity of brushite bone cement

[0087] In Example 1, polyacrylic acid-acrylamide is added to brushite bone cement as an admixture, wherein the mass concentration of polyacrylic acid-acrylamide is 2.5%. The present invention studies the interaction mechanism between polyacrylic acid-acrylamide and brushite bone cement through total organic carbon adsorption experiment and Zeta potential method, and finds that with the addition of polyacrylic acid-acrylamide, the polyacrylic acid-acrylamide adsorbed on the surface of brushite bone cement particles gradually increases, the negative charge on the cement surface also gradually increases, the electrostatic repulsion between particles increases, the cement is more fully dispersed, and the mechanical strength and fluidity of the bone cement are improved. Figure 2 shown.

[0088] Effect evaluation 3 Study on the in vitro bone repair performance of brushite bone cement

[0089] The preparation process of brushite bone cement is the same as that of Example 1. Brushite, hydroxyapatite and polymethyl methacrylate bone cement were prepared into extracts at 0.2 g / mL and cultured with bone marrow mesenchymal stem cells respectively. Then, the in vitro osteogenic activity of different cements was evaluated by alkaline phosphatase staining and alizarin red staining. Figure 3 As shown, brushite bone cement has a better repair effect.

[0090] Effect evaluation 4 Study on the bone repair performance of brushite bone cement in vivo

[0091] The preparation process of brushite bone cement is the same as that of Example 1. In the present invention, brushite, hydroxyapatite and polymethyl methacrylate bone cement are implanted into the lateral femoral condyle defect of rats. Four weeks after the operation, the bone repair effects of different cements are observed by Micro-CT. Figure 4 As shown in the results, brushite bone cement has a better repair effect.

[0092] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A brushite bone cement having energy metabolism regulating function, characterized in that: The brushite bone cement with energy metabolism regulating function is obtained by combining a solid phase and a liquid phase; The solid phase includes β-tricalcium phosphate and monocalcium phosphate, and the liquid phase includes citrate, polyacrylic acid-acrylamide and water.

2. The brushite bone cement having energy metabolism regulating function as claimed in claim 1, characterized in that: The monocalcium phosphate is selected from monocalcium phosphate monohydrate, and the mass ratio of β-tricalcium phosphate to monocalcium phosphate monohydrate is 3-7:3-7.

3. The brushite bone cement having energy metabolism regulating function as claimed in claim 2, characterized in that: The mass ratio of the β-tricalcium phosphate to the calcium dihydrogen phosphate monohydrate is 6:

4.

4. The brushite bone cement having energy metabolism regulating function as claimed in claim 1, characterized in that: In the liquid phase, the concentration of citrate is 0.3-1.0 mol / L.

5. The brushite bone cement having energy metabolism regulating function as claimed in claim 1, characterized in that: In the liquid phase, the concentration of polyacrylic acid-acrylamide is 1-15 wt %.

6. The brushite bone cement having energy metabolism regulating function as claimed in claim 5, characterized in that: In the liquid phase, the concentration of polyacrylic acid-acrylamide is 2.5 wt %.

7. The brushite bone cement having energy metabolism regulating function as claimed in claim 1, characterized in that: The citrate is selected from sodium citrate.

8. The brushite bone cement having energy metabolism regulating function as claimed in claim 1, characterized in that: The solid phase also includes an X-ray blocking agent.

9. The brushite bone cement having energy metabolism regulating function as claimed in claim 8, characterized in that: The X-ray blocking agent is selected from zinc oxide, strontium chloride, strontium bromide, strontium iodide or strontium phosphate.

10. Use of the brushite bone cement with energy metabolism regulation function as claimed in any one of claims 1 to 9 in minimally invasive treatment of orthopedics.

Citation Information

Patent Citations

  • A permeable phosphogypsum bone cement, its preparation method and application

    CN112675358B